Communicative Competence of Secondary School Students of Bhutan - Choeda, Choeda; Gyeltshen, Tashi; Daker, Sonam; Gyeltshen, Sonam; Wangmo, Wangmo; Letho, Dorji (International Journal of Humanities and Education Development (IJHED), 2020)
This study on communicative competence of secondary school students of Bhutan was conducted with the lower, middle and higher secondary school students under four districts Chukha, Samtse, Paro and Thimphu. The study aimed to explore why communicative proficiency was generally perceived low as reported by LaPrarie (2014). Random sampling survey questionnaire was administered to 864 students and purposive sampling interviews conducted with 24 teacher and 2 curriculum developers from Royal Education Council. Other data collection methods included classroom lesson observation and documentary analysis. Simple descriptive analysis for quantitative data and thematic analysis for qualitative data analysis were employed. The study found that majority of the students had low proficiency level in both English and Dzongkha with a few who had higher level. The low communicative competence in both English and Dzongkha has been attributed to the negative influence of social media in which students showed more interested than engaging in academic reading and writing activities. However, the study found the schools organised relevant activities such as literary fest, debates, and speeches, speaking and writing activities to enhance the communication skills. The research recommends activities such as reviewing the curriculum standards, enhancing teachers’ skills to focus on the communicative skills to improve students’ proficiency in communication.